2018
DOI: 10.1057/s41267-018-0153-9
|View full text |Cite
|
Sign up to set email alerts
|

Global connectedness and local innovation in industrial clusters

Abstract: CIRANO Le CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Le financement de son infrastructure et de ses activités de recherche provient des cotisations de ses organisations-membres, d'une subvention d'infrastructure du gouvernement du Québec, de même que des subventions et mandats obtenus par ses équipes de recherche. CIRANO is a private non-profit organization incorporated under the Quebec Companies Act. Its infrastructure and research activities are funded th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 92 publications
(113 reference statements)
1
98
0
2
Order By: Relevance
“…As for the internationalization of the ecosystem itself, i.e., the processes through which entrepreneurial ecosystems become globally connected, to date very little academic research explores these phenomena (e.g., Carvalho, Camacho, Amorim and Esperança [52] that, technically, focuses on the internationalization of a single ecosystem actor, i.e., a start-up accelerator program, rather than that of the ecosystem as a whole). Indeed, most of the extant literature heavily focuses on the connections established across other types of spatial agglomeration of firms-again, primarily clusters and industrial districts, rather than entrepreneurial ecosystems [53][54][55][56][57]-and/or focuses on the connections created due to the flows of physical goods linked to the establishment of Global Value Chains primarily on the part of large multinational firms-and, hence, they are examined through a Supply Chain lens. However, a quite substantial stream of research focuses on the flows of knowledge (rather than of physical goods) across space but, again, either in the context of clusters [58,59] rather than in entrepreneurial ecosystems or in terms of multinational corporations' intra-firm knowledge transfers across borders, i.e., within the context of a single organisation operating across a number of different country locations, that which makes such knowledge flows affected by a peculiar set of purposes and of promoting and hindering factors [60].…”
Section: Literature Overviewmentioning
confidence: 99%
“…As for the internationalization of the ecosystem itself, i.e., the processes through which entrepreneurial ecosystems become globally connected, to date very little academic research explores these phenomena (e.g., Carvalho, Camacho, Amorim and Esperança [52] that, technically, focuses on the internationalization of a single ecosystem actor, i.e., a start-up accelerator program, rather than that of the ecosystem as a whole). Indeed, most of the extant literature heavily focuses on the connections established across other types of spatial agglomeration of firms-again, primarily clusters and industrial districts, rather than entrepreneurial ecosystems [53][54][55][56][57]-and/or focuses on the connections created due to the flows of physical goods linked to the establishment of Global Value Chains primarily on the part of large multinational firms-and, hence, they are examined through a Supply Chain lens. However, a quite substantial stream of research focuses on the flows of knowledge (rather than of physical goods) across space but, again, either in the context of clusters [58,59] rather than in entrepreneurial ecosystems or in terms of multinational corporations' intra-firm knowledge transfers across borders, i.e., within the context of a single organisation operating across a number of different country locations, that which makes such knowledge flows affected by a peculiar set of purposes and of promoting and hindering factors [60].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Например, в [Lorenzen, Mudambi, 2013] доказывается, что в глобальной экономике от характера связей между кластерами зависит развитие кластеров: вглубь (т. е. специализация на одном направлении) или вширь (т. е. диверсификация производства). В работе [Turkina, Van Assche, 2018] обосновывается, что включенность кластера в глобальную сеть и усиление взаимодействия с другими кластерами положительно влияют на его инновационную производительность.…”
Section: теория анализа сетей и обоснование метода исследованияunclassified
“…It has been recently shown that the influence of the 'cluster-of-origin' is far more important than that of the 'country-of-origin' in explaining firms' investment location choices (e.g. Li and Bathelt, 2017;Turkina and Van Assche, 2018), and that localised regional and cluster networks affect the shape of global urban networks (Bathelt and Li, 2014).…”
Section: Globalisation Through Fdi and Geographymentioning
confidence: 99%